2022
DOI: 10.17794/rgn.2022.4.2
|View full text |Cite
|
Sign up to set email alerts
|

Sorption of Oil by Mechanochemicaly Activated Shungite

Abstract: In the paper the sorption capacity of shungite rocks of the Koksu field (Kazakhstan) in relation to the oil from the Karazhanbas and Tengiz fields (Kazakhstan) were studied. Oil spills occurring during production, gathering, transportation, storage and refining, and repair work on wells are an urgent environmental problem. There are effective methods of soil purification, including particular interests addressed to sorption process. The aim of this research is to study oil sorption by shungite rocks of the Kok… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…The mineral adsorbent based on the rock shungite is of particular interest for investigation because it is a resource in the USA (Dead River Basin, Marquette Co., New Hampshire, MI, USA) [ 39 ], Austria (four deposit districts: Tyrol; Salzburg; Styria) [ 40 ], Democratic Republic of the Congo (Kambove District, Upper Katanga)b [ 41 ], India (Kadapa District, Rayalasima Region, Andhra Pradesh) [ 42 ], Ukraine (Mlynkovskoye iron ore district, Krivoi Rog-Kremenchug zone, Ukrainian shield) [ 43 ], Republic of Kazakhstan (Almaty region) [ 44 ], and Russia (Republic of Karelia) [ 45 , 46 , 47 ], where it occurs in a large volume. It is known that there are quite a lot of ways to use it in various sectors of the national economy, such as creating water filters, used as an antioxidant and anti-inflammatory agent in veterinary medicine, and as a sorbent and feed additive.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The mineral adsorbent based on the rock shungite is of particular interest for investigation because it is a resource in the USA (Dead River Basin, Marquette Co., New Hampshire, MI, USA) [ 39 ], Austria (four deposit districts: Tyrol; Salzburg; Styria) [ 40 ], Democratic Republic of the Congo (Kambove District, Upper Katanga)b [ 41 ], India (Kadapa District, Rayalasima Region, Andhra Pradesh) [ 42 ], Ukraine (Mlynkovskoye iron ore district, Krivoi Rog-Kremenchug zone, Ukrainian shield) [ 43 ], Republic of Kazakhstan (Almaty region) [ 44 ], and Russia (Republic of Karelia) [ 45 , 46 , 47 ], where it occurs in a large volume. It is known that there are quite a lot of ways to use it in various sectors of the national economy, such as creating water filters, used as an antioxidant and anti-inflammatory agent in veterinary medicine, and as a sorbent and feed additive.…”
Section: Discussionmentioning
confidence: 99%
“…Polunina et al [ 52 ] studied the influence of thermo- and mechano-chemical modification of the mineral shungite from Karelia (Russian) on its chemical composition and physicochemical properties of their effect on the sorption of toxins and phenols, while the sorption properties of shungite from the Koksu deposit (Kazakhstan) were studied by Ongarbayev et al [ 44 ]. Thus, in the works of Charykova et al [ 47 ], it is shown that the material from the shungite deposit of Zazhoginskoe (Republic of Karelia) contains 30% carbon and 70% silicon.…”
Section: Discussionmentioning
confidence: 99%